Guía metodológica para la aplicación del ajedrez en el fortalecimiento del proceso enseñanza aprendizaje - Recalde Recalde, Erick Arturo (2020)
This research project studies chess as a methodological strategy applied to strengthen values in children; There are studies of this discipline, in which it is shown that it favors lateral thinking, since it allows to contemplate different alternative solutions for a given problem, consequently in the educational field the lack of values was recognized, promoting indiscipline in the fifth year of the Unit Educational "Poaló García Moreno". For this reason, the research focused its objective on the application of a workshop "Guide to the" One for All "Technique for the strengthening of values" in the teaching-learning process, through observation (observation sheet), they collected information on issues inherent to respect, ethics and order. Regarding the methodology, it was framed in a qualitative approach, it is considered a descriptive, documentary and field research; the inductive method was used for this research, as well as the use of techniques; the observation and the interview, with their respective instruments. Based on the results obtained, it is concluded that the students improve both their behavior and their attitudes thanks to the use of the workshop and contribute to the educational process by promoting cordiality in the classroom